Incentive and Output: A Statement of the Place of the Personnel Manager in Modern Industry - Marshall, L. C. (Journal of Political Economy, 1920)
The work of the personnel manager may be seen in perspective by viewing him as one of the entrepreneur's lieutenants in the task of "getting men to work together." This task is, of course, performed in terms of the whole structure of our specialized industrial society.